A new synthesis strategy for chiral CdS nanotubes based on a homochiral MOF template. Issue 27 (4th March 2015) - Kuang, Xuan; Ma, Yu; Zhang, Caiyun; Su, Hao; Zhang, Jine; Tang, Bo
Abstract : We present a convenient and rapid way to prepare helical CdS nanotubes, with a MOF as the template. Abstract : We describe for the first time a convenient technique to prepare helical CdS nanotubes, with a MOF as the template. The prepared helical CdS nanotubes were remarkably sensitive tod /l -aspartic acid (Asp) and can be used as a potential sensor for enantioselective recognition ofd /l -Asp.